Os sentidos e significados das resistências às precarizações do trabalho uberizado - Sousa, Luiz Henrique Morais (2025)
This study examines the senses and meanings of resistance to precarious labor within the context of platform-based work (uberization). Drawing on the theoretical frameworks of Cultural-Historical Psychology and Historical-Dialectical Materialism, this research focuses on contemporary transformations in the world of work, characterized by the advancement of neoliberalism, systemic crises, and capitalist productive restructuring. Uberization emerges as the current manifestation of these transformations, marked by extreme precarity in labor relations, fragmentation of the working class, and the intensification of digitally-mediated control and exploitation mechanisms. The research develops an analysis of platform capitalism's dynamics, demonstrating how structural crises of the capitalist system generate new modalities of flexible accumulation that exacerbate worker precarity. The study combines literature review with qualitative analysis of interviews conducted with app-based delivery workers in Goiânia, Brazil. The Meaning Nuclei methodology enabled exploration of the psychosocial dimensions of resistance, revealing how workers ascribe meaning to their experiences of exploitation and construct both individual and collective strategies of resistance. Findings demonstrate that despite platforms' efforts to individualize and depoliticize labor relations, delivery workers develop forms of resistance ranging from daily acts of insubordination to structured collective organizing. The study identifies critical reinterpretations of labor conditions, practices of class solidarity, and attempts to build collective identities. The analysis shows how the social meanings of resistance intertwine with the subjective significations workers attribute to their struggles, mediated by the concrete material conditions in which they are embedded. The study concludes by emphasizing the importance of a Psychology committed to working-class interests, capable of articulating an understanding of subjective processes with the transformation of exploitative social structures. It reveals that platform workers' resistance maintains continuity with working-class struggle traditions while adapting to contemporary capitalism's new configurations. The research highlights the need for professional practices and academic studies that foster worker organizations and contribute to building collective alternatives to precarity. Thus, the historical and dialectical nature of resistance becomes evident as it evolves to confront transformations in capitalist exploitation, demonstrating the possibility of transforming labor realities.